2013
DOI: 10.3944/aott.2013.2832
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular index values in healthy Turkish children between 6 months and 8 years of age: a cross-sectional radiological study

Abstract: The study defines the normal acetabular index values in healthy Turkish children between 6 months and 8 years of age and the expected acetabular index values for mild and severe dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 5 publications
1
17
0
1
Order By: Relevance
“…We used the average acetabular index 22degree, which ranged from 15-25 degrees as a baseline comparative indicator, as was assessed in the normal side of our 38 unilateral DDH. That range of the acetabular index is within the AI range cited by Ibrahim et al [17].…”
Section: Femalesupporting
confidence: 84%
See 1 more Smart Citation
“…We used the average acetabular index 22degree, which ranged from 15-25 degrees as a baseline comparative indicator, as was assessed in the normal side of our 38 unilateral DDH. That range of the acetabular index is within the AI range cited by Ibrahim et al [17].…”
Section: Femalesupporting
confidence: 84%
“…Since our patients were of both age ranges, thus we have used both these parameters in this study as the parameter for radiological assessment ( Table 5). Ibrahim et al in their study on Turkish children have referred to the mean acetabular index of males in the age group of one and eight years as ranging from 21.0 degrees to 13.8 degrees, with the lowest limit mean from 23.6 to 14.2 degrees [17]. Whereas in females, the mean acetabular index is in the same age group, ranging from 23.6 degrees to 14.2 degrees and the lowest is 33 degrees to 23 degrees.…”
Section: Discussionmentioning
confidence: 99%
“…The variance of AI measurement and pelvic orientation is greater in younger children who are incapable of cooperation during the examination. The reliability and reproducibility of AI measurements have been questioned over many decades [10][11][12]. If an accurate AI measurement could be made from a non-standard pelvic radiograph, this would be a significant gain in the utility of the measurement [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…conducted on 2788 children aged between 6 months and 8 years. 23 In another study, the AI of 1162 patients from Eskişehir region (aged between 5 and 75 years) were measured and was found to be 39.2°±4.6°. 24 In the present study, we found a mean of 37.58°±5.30° in the right hip and 37.80°±4.82° in the left hip.…”
Section: Discussionmentioning
confidence: 96%